Effect of Antioxidant Therapy on Oxidative Stress In Vivo 2021 - Anna Maria Fratta Pasini; Luciano Cominacini (MDPI AG, 2022)
Oxidative stress (OS) is an imbalance between the formation of reactive oxygen and nitrogen species and antioxidant defenses [...]